Surfactant–solid complex for enhancing the flow in pipelines: an experimental approach - Mahmood, Wafaa K.; Abdulkarim, Makarim H.; Abdulbari, Hayder A. (Springer Science and Business Media Deutschland GmbH, 2022)
Background: Viscoelastic soluble polymeric additives have been used successfully for a long time as drag reducers in pipelines carrying commercial liquids like crude oil. Most of these polymers suffer from irreversible degradation when exposed to high shearing zones as in valves, elbows, and pumps which reduces, or eliminates, its flow enhancement effect. Insoluble additives were proven to be an effective drag reducer that overcomes the degradation drawback of soluble additives. On the other hand, insoluble additives suffer from the lack of viscoelasticity which limits their use as flow enhancers. The creation of complexes from soluble and insoluble additives is a field of research that is rarely explored despite its importance in introducing new flow enhancement methods for a higher drag reduction performance. The present work introduces a new surfactant–solid complex as a drag-reducing agent for turbulent flow in pipelines. Results: The surfactant, solid, and their complexes’ drag reduction performance was tested in a closed-loop turbulent flow liquid circulation system, while rheological characteristics of the soluble additives were tested using a standard rheometer. All the surfactant solutions showed non-Newtonian shear thinning behavior in all the investigated concentrations that ranged between 500 and 1300 wppm. The initial experimental result indicated that the surfactant solution’s drag reduction performance was higher than that of the solid suspensions. On the other hand, the drag reduction performance was enhanced by 52% when creating a 1300 wppm surfactant–2000 wppm solid complex. This improvement in the drag reduction performance is due to the formation of surfactant–solid-enforced aggregates with high resistance to shear forces and high turbulence suppression efficiency. Conclusions: The present work introduces a new drag reduction solid–surfactant complex by creating aggregates combining the viscoelastic properties of surfactants with the resistance to high shear forces exerted by the solid particles. The polar nature of the surfactant micelles that form in single-phase flow systems contributed significantly to trapping the solid’s micro-particles as enforcement to resist the shearing forces applied by the turbulent flow system.